EMPOWERING STUDENTS' PANCASILA AWARENESS AND CULTURAL RESILIENCE THROUGH A LOCAL MINANGKABAU-BASED PANCASILA EDUCATION MODULE (PETATAH-PETITIH) - Sunarti, Sunarti (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
Globalization and modernization are now starting to cause concern among the public concerning the preservation of traditional cultural values that exist in Indonesia, where one of the cultures that is starting to disappear among elementary school students is Petatah Petitih Minangkabau. It is necessary to make efforts to preserve this culture, one of which is to develop a module based on Minangkabau local culture (Petatah-Petitih). This research is development research using the 4-D model, Definition (Define), Design (Design), Development (Develop) and Dissemination (Disseminate). The samples in this study were students in class IVc at SDN 01 Lima Kaum with a total of 21 students. Data collection techniques in this study used interviews, questionnaires, and observation. As for the research results, namely the results of product validation by the three validators declared valid, namely the results of validator 1 90.78% in the very valid category, the results of validator 2 88.75% in the very valid category, and the results of validator 3 95.94% in the very valid category. The level of product practicality is also in the very practical category, namely in the student practicality test the score is 84.25% and the teacher's practicality test is 95%. In addition, because the module developed is an integration of Minangkabau culture, the level of student cultural resilience is at 88.10% in the very good category after using the module. There are 6 dimensions of the Pancasila profile that emerge in students through the use of the Minangkabau Local Culture-Based Pancasila Education Module (Petatah-Petitih). It can be concluded that the development of the Minangkabau Local Culture-Based Pancasila Education Module (Petatah-Petitih) can strengthen the Pancasila profile and cultural resilience of students.